2021
DOI: 10.1007/s00415-021-10731-2
|View full text |Cite
|
Sign up to set email alerts
|

Case report: cerebral sinus vein thrombosis in two patients with AstraZeneca SARS-CoV-2 vaccination

Abstract: SARS-CoV-2 infection is associated with an increased rate of thromboembolic events and mortality. Different vaccines are globally used to limit the pandemic. In this report, we present the case of two young female patients with newly diagnosed cerebral sinus vein thrombosis occurring after injection of the vector-based ChAdOx1 vaccine. Both patients presented with unusual headache only. The two of them used an estrogen-containing contraception, had had a history of deep venous thrombosis, and both had MTHFR mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This description was a probable VITT case, given the lack of anti-PF4 positivity. Another paper from Germany has reported two women presenting with cerebral sinus vein thrombosis after the ChAdOx1 vaccine, each carrying an MTHFR variant (heterozygous A1298C and homozygous MTHFR C677T variant) ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…This description was a probable VITT case, given the lack of anti-PF4 positivity. Another paper from Germany has reported two women presenting with cerebral sinus vein thrombosis after the ChAdOx1 vaccine, each carrying an MTHFR variant (heterozygous A1298C and homozygous MTHFR C677T variant) ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, only three publications regarding thromboembolic adverse effects after the COVID-19 vaccination have published incidents [26][27][28]. Three patients received mRNAbased vaccine and one patient received vector-based vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Early case reports of novel coronavirus pneumonia showed that up to 50% of patients had underlying diseases, and 40% of them had cardiovascular or cerebrovascular diseases (Xiong et al, 2020). There have been clinical studies reporting newly diagnosed cases of cerebral sinus vein thrombosis in patients with MTHFR mutations following injection of the vector-based ChAdOx1 COVID-19 vaccine (Fousse et al, 2022). Folic acid can minimize plasma homocysteine concentrations, thereby reducing risk factors for vascular disease.…”
Section: Discussionmentioning
confidence: 99%